ナンキョク ニヨル プラズマ ハドウ ジッケン - 松本, 紘; マツモト, ヒロシ; 木村, 磐根; キムラ, イワネ; MATSUMOTO, Hiroshi; KIMURA, Iwane (国立極地研究所, 1975)
P(論文) Some important points on the plasma wave experiments in the polar ionosphere are indicated. Concrete proposals of the antarctic rocket experiments on the plasma waves are given. One is a passive observation of the plasma waves and the others are active experiments of linear and nonlinear wave-particle and wave-wave interactions. departmental bulletin paper